2022
DOI: 10.1155/2022/6441179
|View full text |Cite|
|
Sign up to set email alerts
|

Multifunctional Drug-Loaded Phase-Change Nanoparticles Inhibit the Epithelial-Mesenchymal Transition of Hepatocellular Carcinoma by Affecting the Activity of Activated Hepatic Stellate Cells

Abstract: Objectives. Preparation of a multifunctional drug-loaded phase-change nanoparticle (NP), pirfenidone perfluoropentane liposome NPs (PPL NPs), and combined with low-intensity focused ultrasound (LIFU) to influence epithelial mesenchymal transition (EMT) for hepatocellular carcinoma (HCC) by inhibiting the activity of activated Hepatic Stellate Cells (a-HSCs). Methods. PPL NPs were prepared by the thin film dispersion method. The appearance, particle size, zeta potential, encapsulation efficiency, drug loading r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%